2023
DOI: 10.1192/j.eurpsy.2023.2407
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 on European healthcare provision for working-age adults with major depressive disorder

Abstract: Background Major depressive disorder (MDD) is a leading cause of disability worldwide, and yet delivery of care for this illness is rife with gaps. The COVID-19 pandemic has had far reaching implications for every facet of healthcare, and MDD is no exception. This scoping review aimed to ascertain the impacts of COVID-19 on the delivery of MDD care in Europe, as well as to evaluate any novel MDD care strategies trialled in this period. Methods We searched the PubMed and PsycINFO database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Only about 19% of those diagnosed with MDD access psychiatric care, and an even smaller percentage access specialized mood disorder care. The theme of gaps in care pathways was further pursued by Wong et al [ 3 ] in the context of the COVID-19 pandemic. The authors found that information on the impact of the pandemic on treatment pathways for MDD was incomplete.…”
mentioning
confidence: 99%
“…Only about 19% of those diagnosed with MDD access psychiatric care, and an even smaller percentage access specialized mood disorder care. The theme of gaps in care pathways was further pursued by Wong et al [ 3 ] in the context of the COVID-19 pandemic. The authors found that information on the impact of the pandemic on treatment pathways for MDD was incomplete.…”
mentioning
confidence: 99%